The origins of Ireland's holy wells - Ray, R. Celeste, (Archaeopress, 2014)
This work re-assesses archaeological research into holy well sites in Ireland and the evidence for votive deposition at watery sites throughout northwest European prehistory. Ray examines a much-ignored and diminishing archaeological resource; moving beyond debates about the possible Celticity of these sites in order to gain a deeper understanding of patterns among sacred watery sites. The text considers how and why sacred springs are archaeologically-resistant sites and what has actually been found at the few excavated in Ireland.